The recondites of modernity: history and utopia in Kant and Adorno - Duarte Araújo, Alan (2024)
This paper aims to elucidate the meanings of the concept of modernity, highlighting its contradictory core and the theoretical and practical implications of this contradiction. To this end, we turn to the works of the German philosopher Immanuel Kant (1724-1804), as a paradigmatic intellectual expression of modernity, insofar as the author highlights notions that seem central to understanding the specificity of his time, which are brought together in his reflections on history and human progress, in the context of the enlightenment that is struggling to become effective. We believe it is possible to extract from these reflections an idea of utopia which, although it needs to be cleansed of certain idealistic excesses, ends up representing a perspective that dialogues with Critical Theory, notably with Theodor Adorno (1903-1969). Although he demonstrates the bankruptcy and limits of the philosophical categories that authors such as Kant used to think about modernity, he doesn't discard the concepts in question, but rather puts them under tension, ultimately aiming to unveil the prospects for emancipation from the administered world, which, in the final analysis, have always been present at the heart of modern thought.